MAINSTREAMING IDEA: ALTERNATIVE READING OF STATE AND CIVIL SOCIETY RELATION IN POLICY MAKING - Seftyono, Cahyo; Santoso, Purwo; Darwin, Muhadjir Muhammad; Hadna, Agus Heruanto (CosmoGov: Jurnal Ilmu Pemerintahan, 2020)
Scientific climate as the unity of ideas and the activator of an organization is suspected to be a form of civil society leadership. It moves from the personification of actors to the debate of ideas. Civil society as a political movement is a study that still being debated because of its position when faced with the state and policy. This article provides a different review, by carrying out the phenomenon of research-based policy in Indonesia. Through qualitative data tracking, it was shown that some civil society did not put themselves in these two positions, namely as the opponent or the partner for the government. Furthermore, the reality showed that both of them, in this case civil society and the state were more concerned with the realization of their ideas, the openness, and the professionalism of publications to support policy making. More specifically, the existence of openness and implementation of science and information as a collaborative arena appeared from the interaction of the National Development Planning Agency and Knowledge Sector Initiative which had been running since 2011 in building the ecosystem of Research- Based Policy. Then, it was followed by the presence of Open Science community in 2017 and the establishment of National Research and Innovation Agency in 2019. Therefore, both collaborations encouraged the creation of a data openness climate in policy making. This was a general norm, but it did not work fully. Moreover, this article provides a space that the opportunities to strengthen the ecosystem of research-based policy can be optimized by setting out the idea approach and makes the civil society goes beyond the institutional barrier gb777